(untitled) (Research, Society and Development, 2022)
Health promotion at school aims to develop knowledge about health, besides values, skills and important practices for a healthy life. This action seeks to empower people to change for the benefit of their own health and the community. This study aims to report goals of health promotion in a private school of Rio Grande do Sul. This is an experience report that addresses the study is about projects that guide the pedagogical work of the group of teachers, assessments, nutritional intervention and physical fitness measures in students, avoiding vulnerabilities in order to contribute to their integral and autonomous development. The authors explain the daily school life and the health promotion strategies managed at school, in an attempt to reduce vulnerabilities and help in the integral education of students. It was observed that health promotion actions in school environment are possible and can be carried out effectively and permanently. However, the strategies reported are initiatives based on education and health practices, seeking to build participatory and healthy environments at school, it is not the intention of this report to present itself as the only experience or model of health promotion at school, but to encourage dialogue about experiences and practices in the school environment, highlighting the actors involved.